Resumindo e concluindo... Em busca da fase perdida - Sílvio Almeida Abrantes Moreira (2009)
This text is about MPSK and QAM carrier phase recovery techniques. Only digital feedforward Data-Aided and Non-Data-Aided Maximum Likelihood methods are addressed.